PA / ABS (polyamide / acrylonitrile-butadiene-styrene) alloy material as well as preparation method and application thereof

By combining antibacterial glass fiber loaded with silver ion antibacterial agent in PA/ABS alloy material with PA6 resin, combined with the preparation method of the twin screw extrusion mechanism, the problems of material strength and antibacterial effect are solved, and high strength and long-term effect are achieved Antibacterial effect is suitable for automotive interior and exterior decoration and other fields.

CN119286246APending Publication Date: 2025-01-10TIANJIN KINGFA NEW MATERIAL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411567827.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing PA/ABS alloy materials have low strength and poor long-term antibacterial effects, making it difficult to effectively reduce cross-infection among passengers on public transportation.

Method used

Antibacterial glass fiber containing silver ion antibacterial agent is used to combine with PA6 resin to achieve long-term antibacterial effect through the loading and transfer of silver ion antibacterial agent, and the mechanical properties and heat resistance of the material are improved through the twin-screw extrusion mechanism.

Benefits of technology

It has achieved high strength and long-term antibacterial effects of PA/ABS alloy materials, broadened its application range, and has excellent performance in the field of automotive interior and exterior decoration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005119716510000071
    Figure BDA0005119716510000071
  • Figure BDA0005119716510000072
    Figure BDA0005119716510000072
  • Figure BDA0005119716510000081
    Figure BDA0005119716510000081
Patent Text Reader

Abstract

The invention relates to a PA / ABS (polyamide / acrylonitrile-butadiene-styrene) alloy material as well as a preparation method and application thereof, and belongs to the technical field of high polymer materials. The PA / ABS alloy material disclosed by the invention is prepared from the following components in parts by weight: 49 to 71 parts of PA6 resin, 19 to 48 parts of ABS resin, 4 to 21 parts of antibacterial glass fiber, 0.15 to 5.5 parts of processing aid and 0.08 to 1.2 parts of carbon black, the melt index of the PA6 resin is 5 to 20 g / 10 min; the antibacterial glass fiber comprises a silver ion antibacterial agent, and the mass percent of the silver ion antibacterial agent in the antibacterial glass fiber is 2%-4%. The antibacterial glass fiber containing the silver ion antibacterial agent is adopted in the PA / ABS alloy material, so that the alloy material has a long-acting antibacterial effect, and meanwhile, the antibacterial glass fiber is compounded with the PA6 resin with a specific melt index, so that the mechanical property and the heat resistance of the material are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a PA / ABS alloy material and a preparation method and application thereof. Background Art

[0002] Since the 21st century, major infectious diseases have broken out many times around the world, including severe acute respiratory syndrome (SARS), influenza A (H1N1), poliomyelitis, Ebola virus disease, Middle East respiratory syndrome (MERS), etc., causing global public health events and having a huge impact on human society, economy and politics.

[0003] At present, the public pays more and more attention to their own protection against infectious diseases, which requires us to actively develop biosafety materials. PA / ABS alloy materials have a unique matte effect, excellent heat resistance and processing performance, and are wear-resistant and chemical-resistant, and are often used in the field of automotive interior and exterior decoration. However, the strength of the current PA / ABS alloy materials is not high, and the long-term antibacterial effect is poor. Giving them long-term antibacterial function can effectively reduce the cross-infection phenomenon of passengers on public transportation (such as taxis, buses, trains, etc.).

[0004] Therefore, it is of great significance to prepare a PA / ABS alloy material with high strength and long-lasting antibacterial effect. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a PA / ABS alloy material and a preparation method and application thereof.

[0006] The present invention is achieved through the following technical solutions:

[0007] In a first aspect, the present invention provides a PA / ABS alloy material, comprising the following components by weight: 49-71 parts of PA6 resin, 19-48 parts of ABS resin, 4-21 parts of antibacterial glass fiber, 0.15-5.5 parts of processing aid, and 0.08-1.2 parts of carbon black; the PA6 resin has a melt index of 5-20 g / 10 min at 235° C. and a weight of 2.16 kg according to ISO1133-2012; the antibacterial glass fiber comprises a silver ion antibacterial agent, and the mass percentage of the silver ion antibacterial agent in the antibacterial glass fiber is 2%-4%.

[0008] The PA / ABS alloy material of the present invention adopts antibacterial glass fiber containing silver ion antibacterial agent. Since the silver ion antibacterial agent is loaded in the glass fiber, the antibacterial agent itself is not easy to migrate and precipitate, but the silver ions with antibacterial effect can be transmitted through the glass fiber network, so that the alloy material obtains a long-lasting antibacterial effect. At the same time, the antibacterial glass fiber is compounded with a PA6 resin with a melt index of 5-20g / 10min, which effectively improves the mechanical properties and heat resistance of the material and broadens the application range of the PA / ABS alloy material.

[0009] In the PA / ABS alloy material of the present invention, the weight percentage of the PA6 resin is any one of 49 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, and 71 parts, or both of the range values; the weight percentage of the ABS resin is any one of 19 parts, 20 parts, 30 parts, 40 parts, 45 parts, 47 parts, and 48 parts, or both of the range values.

[0010] Preferably, the PA / ABS alloy material comprises the following components by weight: 50-70 parts of PA6 resin, 20-47 parts of ABS resin, 5-20 parts of antibacterial glass fiber, 0.2-5 parts of processing aid, and 0.1-1 parts of carbon black.

[0011] Preferably, the PA6 resin has a melt index of 10-15 g / 10 min at 235° C. and a weight of 2.16 kg according to ISO 1133-2012.

[0012] The melt index of PA6 resin will affect the comprehensive performance of the material. The melt index reflects the molecular weight of PA6. The lower the melt index, the larger the molecular weight, and the mechanical properties and heat resistance of the material are improved to a certain extent, but the processing fluidity will be relatively reduced; the higher the melt index, the smaller the molecular weight, the material has better processing fluidity, but the mechanical properties and heat resistance may not be guaranteed. Therefore, its range is limited here. The present invention preferably prefers PA6 resin with a melt index of 5-20g / 10min, and more preferably, the melt index of PA6 resin is 10-15g / 10min.

[0013] Preferably, in the ABS resin, the acrylonitrile content is 15wt%-35wt%, the butadiene content is 5wt%-30wt%, and the styrene content is 40wt%-60wt%.

[0014] ABS resin is the base resin that accounts for a relatively large proportion in the product of the present invention. The content of its components has an impact on the performance and surface appearance of the product. It has been verified that when the content of each component in the ABS resin in the product is preferably within the above range, the obtained product can obtain better mechanical properties and good appearance.

[0015] The ABS resin used in the present invention may be either emulsion ABS or bulk ABS. Preferably, the ABS resin has a melt index of 5-25 g / 10 min at 220° C. and a weight of 10 kg according to ISO1133-2012; more preferably, the ABS resin has a melt index of 12-18 g / 10 min at 220° C. and a weight of 10 kg according to ISO1133-2012.

[0016] Preferably, the average particle size of the butadiene rubber phase in the ABS resin is 100 nm to 500 nm, wherein the particle size of the butadiene rubber phase is statistically obtained by electron microscope observation after solvent etching.

[0017] More preferably, the average particle size of the butadiene rubber phase in the ABS resin is 200 nm-300 nm.

[0018] Preferably, the antibacterial glass fiber is obtained by mixing glass raw materials with silver ion antibacterial agent, melting, cooling, drawing and cutting. The glass raw materials can be glass products, such as glass bottles, glass windows and the like.

[0019] The raw materials of the antibacterial glass fiber of the present invention can be recycled glass products such as glass bottles and glass windows, which has certain environmental protection significance.

[0020] Preferably, the melting temperature is 1400°C-1600°C, and the time is 0.5h-1h; preferably, the melted and homogenized glass liquid is passed through a 4000-hole platinum leak plate and simultaneously drawn using a wire drawing machine to prepare glass fiber, and the drawing temperature is 1000°C-1300°C.

[0021] Preferably, the antibacterial glass fiber is chopped into strands using a chopped fiber machine, and has an average diameter of 6 μm-10 μm and an average length of 0.5 mm-1.0 mm.

[0022] Preferably, the processing aid includes at least one of an antioxidant, a lubricant, a coupling agent, and a compatibilizer.

[0023] Preferably, the antioxidant comprises a primary antioxidant and a secondary antioxidant, the primary antioxidant comprises a hindered phenol antioxidant and / or an aromatic amine antioxidant, and the secondary antioxidant comprises a phosphite antioxidant and / or a thioether secondary antioxidant.

[0024] Preferably, the lubricant includes at least one of EBS, stearic acid, butyl stearate, and oleamide.

[0025] Preferably, the coupling agent comprises a silane coupling agent.

[0026] Preferably, the compatibilizer includes at least one of a styrene-acrylonitrile-maleic anhydride terpolymer and a maleic anhydride grafted compatibilizer.

[0027] Preferably, the carbon black includes at least one of carbon black powder and carbon black masterbatch.

[0028] Preferably, the carbon black masterbatch uses polyethylene as a carrier and has a carbon black content of 40wt%-60wt%.

[0029] More preferably, the processing aid includes an antioxidant, a lubricant, a coupling agent and a compatibilizer; wherein the weight portion of the antioxidant is 0.05-0.5 parts, the weight portion of the lubricant is 0.025-0.25 parts, the weight portion of the coupling agent is 0.025-0.25 parts, and the weight portion of the compatibilizer is 0.1-4 parts.

[0030] Preferably, in the PA / ABS material, the sum of the mass percentages of the ABS resin and the PA6 resin is not less than 75%.

[0031] In a second aspect, the present invention provides a method for preparing the PA / ABS alloy material, comprising the following steps:

[0032] (1) uniformly mixing PA6 resin, ABS resin, processing aid and carbon black according to the above-mentioned parts by weight to obtain a premix;

[0033] (2) placing the premix obtained in step (1) at the main feed port of a twin-screw extruder, feeding the antibacterial glass fiber to the side, melt-extruding, granulating and drying, thereby obtaining the PA / ABS alloy material.

[0034] The components of the PA / ABS material of the present invention are transported, heated and sheared in a twin-screw extruder, so that the materials are fully melted and compounded, and then extruded, granulated and dried to obtain the PA / ABS alloy material. The preparation method of the present invention is simple and can realize industrial-scale production.

[0035] Preferably, in step (1), the mixing is performed using a high-speed mixer, the rotation speed of the high-speed mixer is 200 r / min-800 r / min, and the stirring time is 3 min-10 min.

[0036] Preferably, in step (2), the twin-screw extruder is divided into twelve temperature zones, the temperature is 30°C-300°C, the screw speed is 250-350 rpm, and the aspect ratio is (38-50):1.

[0037] In a third aspect, the present invention provides application of the PA / ABS alloy material in automobile interior and exterior decoration.

[0038] The PA / ABS alloy material of the present invention can be used for automobile interior and exterior decoration parts and components such as automobile central control panel, instrument panel cover, air-conditioning outlet, door panel center trim, window lift cover, and body trim.

[0039] The present invention has the following beneficial effects: the present invention provides a PA / ABS alloy material, which introduces antibacterial glass fiber with silver ion antibacterial agent so that the antibacterial agent can be released for a long time and has a long-lasting antibacterial effect. At the same time, the antibacterial glass fiber is compounded with PA6 resin, so that the alloy material has excellent strength and other mechanical properties. DETAILED DESCRIPTION

[0040] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0041] Unless otherwise specified, the experimental methods used in the examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.

[0042] Examples 1-11

[0043] The composition of the PA / ABS alloy material described in the embodiment of the present invention is shown in Table 1.

[0044] The preparation method of the PA / ABS alloy material comprises the following steps:

[0045] (1) premixing PA6 resin, ABS resin, processing aid and carbon black according to the weight proportions and then transferring them into a high-speed mixer for stirring and mixing uniformly to obtain a premix; the stirring speed of the high-speed mixer is 400 r / min, and the stirring time is 8 min;

[0046] (2) placing the premix obtained in step (1) at the main feed port of a twin-screw extruder, feeding the antibacterial glass fiber to the side, melt-extruding, granulating and drying, thereby obtaining the PA / ABS alloy material.

[0047] The melt extrusion conditions are as follows: the temperatures of the twelve temperature zones are 30°C-200°C-260°C-260°C-270°C-280°C-280°C-300°C-300°C-280°C-300°C-300°C, the screw speed is 300 rpm; and the aspect ratio of the twin-screw extruder is 40:1.

[0048] Comparative Examples 1-7

[0049] The difference between Comparative Examples 1-7 and the embodiment is only in the types and proportions of components, as shown in Table 2. In the preparation method of Comparative Example 7, the silver ion antibacterial agent is blended with the remaining components in step (1) to obtain a premix.

[0050] Among the components described in each embodiment and comparative example,

[0051] The PA6 resin-1 is: PA6 VOLGAMID27, Kuibyshev nitrogen, with a melt index of 10 g / 10 min at 235° C. and a weight of 2.16 kg;

[0052] The PA6 resin-2 is: PA6 HY2800A, Haiyang, Jiangsu, with a melt index of 15g / 10min at 235°C and a weight of 2.16kg;

[0053] The PA6 resin-3 is: PA6 M3400, Xinhui Meida, with a melt index of 5 g / 10 min at 235° C. and a weight of 2.16 kg;

[0054] The PA6 resin-4 is: HY-2500A, Haiyang, Jiangsu, with a melt index of 20g / 10min at 235°C and a weight of 2.16kg;

[0055] The PA6 resin-5 is: PA6 BL40H, Baling Petrochemical, with a melt index of 3 g / 10 min at 235° C. and a weight of 2.16 kg;

[0056] The PA6 resin-6 is: PA6 M2400, Xinhui Meida, with a melt index of 30 g / 10 min at 235° C. and a weight of 2.16 kg;

[0057] The PA66 resin is: PA66 EP-158, Huafeng, with a melt index of 10 g / 10 min at 235° C. and a weight of 2.16 kg;

[0058] The ABS resin-1 is: ABS 8434, Sinopec Gaoqiao; the melt index is 18g / 10min at 220°C and 10kg weight; wherein the acrylonitrile content is 20wt%, the butadiene content is 30wt%, and the styrene content is 50wt%; the average particle size of the butadiene rubber phase is 200nm-300nm;

[0059] The ABS resin-2 is: ABS PA-757, Taiwan Chimei, with a melt index of 18g / 10min at 220°C and a weight of 10kg; wherein the acrylonitrile content is 25wt%, the butadiene content is 20wt%, and the styrene content is 55wt%; the average particle size of the butadiene rubber phase is 100nm;

[0060] The ABS resin-3 is: ABSD-120S, Guoqiao Petrochemical, with a melt index of 12g / 10min at 220°C and a weight of 10kg; wherein the acrylonitrile content is 35wt%, the butadiene content is 5wt%, and the styrene content is 60wt%; the average particle size of the butadiene rubber phase is 500nm;

[0061] The antibacterial glass fiber-1 has an average diameter of 6 μm, an average length of 1.0 mm, and a silver ion antibacterial agent content of 3 wt %. The antibacterial glass fiber-1 is mixed with the silver ion antibacterial agent through a glass bottle, melted at 1500° C., and the molten and homogenized glass liquid is passed through a 4000-hole platinum plate and simultaneously drawn by a wire drawing machine to prepare the glass fiber, and the drawing temperature is 1150° C.

[0062] The antibacterial glass fiber-2 has an average diameter of 10 μm, an average length of 0.5 mm, and a silver ion antibacterial agent content of 3 wt %. The antibacterial glass fiber-2 is mixed with the silver ion antibacterial agent through a glass bottle, melted at 1500° C., and the molten and homogenized glass liquid is passed through a 4000-hole platinum plate and simultaneously drawn by a wire drawing machine to prepare the glass fiber, and the drawing temperature is 1150° C.

[0063] The antibacterial glass fiber-3 has an average diameter of 6 μm, an average length of 1.0 mm, and a silver ion antibacterial agent content of 2 wt%. The antibacterial glass fiber-3 is mixed with the silver ion antibacterial agent through a glass bottle, melted at 1500° C., and the molten and homogenized glass liquid is passed through a 4000-hole platinum plate and simultaneously drawn by a wire drawing machine to prepare the glass fiber, and the wire drawing temperature is 1150° C.

[0064] The antibacterial glass fiber-4 has an average diameter of 6 μm, an average length of 1.0 mm, and a silver ion antibacterial agent content of 4 wt%. The antibacterial glass fiber-4 is mixed with the silver ion antibacterial agent through a glass bottle, melted at 1500° C., and the molten and homogenized glass liquid is passed through a 4000-hole platinum plate and simultaneously drawn by a wire drawing machine to prepare the glass fiber, and the drawing temperature is 1150° C.

[0065] The antibacterial glass fiber-5 has an average diameter of 6 μm, an average length of 1.0 mm, and a silver ion antibacterial agent content of 1 wt%. The antibacterial glass fiber-5 is mixed with the silver ion antibacterial agent through a glass bottle, melted at 1500° C., and the molten and homogenized glass liquid is passed through a 4000-hole platinum plate and simultaneously drawn by a wire drawing machine to prepare the glass fiber, and the drawing temperature is 1150° C.

[0066] The antibacterial glass fiber-6 has an average diameter of 6 μm and an average length of 1.0 mm, and the content of the zinc oxide antibacterial agent is 3 wt %. The antibacterial glass fiber-6 is mixed with the zinc oxide antibacterial agent through a glass bottle, melted at 1500° C., and the molten and homogenized glass liquid is passed through a 4000-hole platinum plate and simultaneously drawn by a wire drawing machine to prepare the glass fiber, and the wire drawing temperature is 1150° C. The zinc oxide antibacterial agent is JDGQP-005, from Xiamen Jinda Technology;

[0067] The silver ion antibacterial agent is JDGKP-004, Xiamen Jinda Technology;

[0068] The glass fiber has an average diameter of 6 μm and an average length of 1.0 mm. The glass fiber is melted at 1500° C. through a glass bottle, and the molten and homogenized glass liquid is passed through a 4000-hole platinum plate and simultaneously drawn by a wire drawing machine to prepare the glass fiber. The drawing temperature is 1150° C.

[0069] The antioxidant is composed of a primary antioxidant 1010 and a secondary antioxidant 168 in a mass ratio of 1:2, from Sanfeng Chemical;

[0070] The lubricant is EBS, Japan Kao;

[0071] The coupling agent is silane coupling agent KH550, Shandong Yunsheng Chemical;

[0072] The compatibilizer is styrene-acrylonitrile-maleic anhydride terpolymer SMA-800, produced by Jiaxing Huawen Chemical;

[0073] The carbon black is a carbon black masterbatch with PE as a carrier, and the carbon black content is 50wt%, Cabot;

[0074] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0075] Table 1 Content of each component in the materials of Examples 1-11 (parts)

[0076]

[0077] Table 2 Content of each component in the materials of Comparative Examples 1-7 (parts)

[0078]

[0079]

[0080] The PA / ABS alloy materials prepared in the embodiments and comparative examples were subjected to the following performance tests, as follows:

[0081] 1. Breaking strength: Tested according to GB / T 1039-1992, test rate 50mm / min.

[0082] 2. Bending strength: Tested according to GB / T 9341-2008, test rate 2mm / min.

[0083] 3. Flexural modulus: tested according to GB / T 9341-2008, test rate 2mm / min.

[0084] 4.HDT: GBT 1634-2004 Plastics bending load heat deformation temperature test method, 0.45MPa.

[0085] 5. E. coli killing rate: GB 21551.2-2016

[0086] 6. Staphylococcus aureus killing rate: GB 21551.2-2016

[0087] The test results are shown in Tables 3 and 4.

[0088] Table 3 Material performance test results of Examples 1-11

[0089]

[0090]

[0091] Table 4 Material performance test results of Comparative Examples 1-7

[0092] Test items Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Breaking strength(MPa) 78 158 147 168 152 170 171 Bending strength(MPa) 125 217 205 227 119 122 121 Flexural modulus (MPa) 3400 7140 6900 7480 6980 7120 7150 HDT(℃) 112 124 120 127 117 121 127 Escherichia coli killing rate (%) 25 99 99 98 99 99 96 Staphylococcus aureus killing rate (%) 25 99 99 98 99 99 96

[0093] The PA / ABS alloy materials prepared in each embodiment and comparative example were subjected to a long-term antibacterial test. The test method was to age the materials under a xenon lamp for 192 hours and compare the antibacterial effects. The test results are shown in Tables 5 and 6.

[0094] Table 5 Long-term antibacterial performance test results of materials in Examples 1-11

[0095]

[0096] Table 6 Test results of long-term antibacterial performance of materials in comparative examples 1-7

[0097] Aging time Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 0h 25 99 99 98 99 99 96 48h 24 99 99 98 99 95 96 96h 27 99 99 98 99 90 97 144h 22 99 99 98 99 88 96 192h 25 99 99 98 99 82 96

[0098] It can be seen from the test results in Tables 3-6 that the PA / ABS alloy material of the present invention has excellent long-term antibacterial effect and excellent mechanical properties, with a breaking strength of more than 150 MPA, a bending strength of more than 210 MPA, a bending modulus of at least 7200 MPA, a HDT of at least 118°C, and a long-term sterilization rate of at least 95% for 192 hours.

[0099] It can be seen from Comparative Example 1 that the antibacterial properties of the alloy material are significantly reduced due to the lack of antibacterial glass fiber. In Comparative Examples 2 and 3, the melt index of PA6 resin is not good, resulting in a decrease in the mechanical properties of the material. In Comparative Example 4, the content of silver ion antibacterial agent in the antibacterial glass fiber is not good, resulting in a slight difference in the antibacterial effect of the material. In Comparative Example 5, PA66 is used as the matrix resin, and the overall performance of the material is not as good as that of Example 1. In Comparative Example 6, the antibacterial agent and glass fiber are added separately, resulting in a decrease in the long-term antibacterial effect. In Comparative Example 7, zinc oxide antibacterial agent is used to replace the silver ion antibacterial agent, resulting in a decrease in the antibacterial effect.

[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A PA / ABS alloy material, characterized in that: The invention comprises the following components by weight: 49-71 parts of PA6 resin, 19-48 parts of ABS resin, 4-21 parts of antibacterial glass fiber, 0.15-5.5 parts of processing aid, and 0.08-1.2 parts of carbon black; the PA6 resin has a melting index of 5-20 g / 10 min at 235° C. and a weight of 2.16 kg according to ISO1133-2012; the antibacterial glass fiber comprises a silver ion antibacterial agent, and the mass percentage of the silver ion antibacterial agent in the antibacterial glass fiber is 2%-4%.

2. The PA / ABS alloy material according to claim 1, characterized in that: The PA6 resin has a melt index of 10-15 g / 10 min at 235° C. and a weight of 2.16 kg according to ISO 1133-2012.

3. The PA / ABS alloy material according to claim 1, characterized in that: In the ABS resin, the acrylonitrile content is 15wt%-35wt%, the butadiene content is 5wt%-30wt%, and the styrene content is 40wt%-60wt%.

4. The PA / ABS alloy material according to claim 1, characterized in that: The ABS resin has a melt index of 5-25 g / 10 min at 220° C. and a weight of 10 kg according to ISO 1133-2012.

5. The PA / ABS alloy material according to claim 1, characterized in that: The antibacterial glass fiber has an average diameter of 6 μm-10 μm and an average length of 0.5 mm-1.0 mm.

6. The PA / ABS alloy material according to claim 1, characterized in that: The processing aid includes at least one of an antioxidant, a lubricant, a coupling agent, and a compatibilizer.

7. The PA / ABS alloy material according to claim 6, characterized in that: The antioxidant includes a primary antioxidant and an auxiliary antioxidant. The primary antioxidant includes a hindered phenol antioxidant and / or an aromatic amine antioxidant, and the auxiliary antioxidant includes a phosphite antioxidant and / or a thioether auxiliary antioxidant.

8. The PA / ABS alloy material according to claim 6, characterized in that: The lubricant includes at least one of EBS, stearic acid, butyl stearate, and oleamide; and / or the coupling agent includes a silane coupling agent; and / or the compatibilizer includes at least one of a styrene-acrylonitrile-maleic anhydride terpolymer and a maleic anhydride grafted compatibilizer; and / or the carbon black includes at least one of a carbon black powder and a carbon black masterbatch.

9. The method for preparing the PA / ABS alloy material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) uniformly mixing PA6 resin, ABS resin, processing aid and carbon black according to the above-mentioned parts by weight to obtain a premix; (2) placing the premix obtained in step (1) at the main feed port of a twin-screw extruder, feeding the antibacterial glass fiber to the side, melt-extruding, granulating and drying, thereby obtaining the PA / ABS alloy material.

10. Use of the PA / ABS alloy material according to any one of claims 1 to 8 in automobile interior and exterior decoration.